First we need to convert the equation to standard form:
#-color(red)(6m^2) + 14m^2 - color(blue)(7m) + 1 = -color(red)(6m^2) + 6m^2 + 7m - color(blue)(7m)#
#(-color(red)(6) + 14)m^2 - 7m + 1 = 0 + 0#
#8m^2 - 7m + 1 = 0#
Now, we can use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(8)# for #color(red)(a)#
#color(blue)(-7)# for #color(blue)(b)#
#color(green)(1)# for #color(green)(c)# gives:
#x = (-color(blue)((-7)) +- sqrt(color(blue)((-7))^2 - (4 * color(red)(8) * color(green)(1))))/(2 * color(red)(8))#
#x = (color(blue)(7) +- sqrt(color(blue)(49) - 32))/16#
#x = (7 +- sqrt(17))/16#